Serum Omentin-1 as a Disease Activity Marker for Crohn's Disease. (10th February 2014) - Lu, Yan; Zhou, Li; Liu, Lifeng; Feng, Yan; Lu, Li; Ren, Xiaoyan; Dong, Xinqian; Sang, Weiwei
Abstract : Background and Aim . It remains challenging to determine the inflammatory activity in Crohn's disease (CD) for lack of specific laboratory markers. Recent studies suggest that serum omentin-1 is associated with inflammatory response. We aimed to assess the potential of serum omentin-1 as a marker of disease activity in CD patients. Methods . Serum omentin-1 concentrations were determined by enzyme-linked immunosorbent assay (ELISA) in patients with CD (n = 240 ), functional gastrointestinal disorders (FGDs, n = 120 ), and healthy controls (HC, n = 60 ) and evaluated for correlation with disease activity. Expression of omentin-1 in colonic tissues from patients with CD was also analyzed by real-time PCR and Western blotting. Serum omentin-1 levels as an activity index were evaluated using a receiver operating characteristic (ROC) curve. Results . Serum omentin-1 concentrations were significantly decreased in active CD patients compared with patients in remission, FGDs, and HC (all P < 0.001 ). Expression of omentin-1 was decreased at mRNA and protein levels in inflamed colonic tissues in active CD than that in noninflamed colonic tissues. Serum omentin-1 levels were negatively correlated with disease activity in CD, better than C-reactive protein (CRP). Conclusion . Our results indicate that serum and colonic omentin-1 expressions are decreased in active CD patients. The correlation of serum omentin-1 with disease activity in CD is superior to that of CRP. Serum omentin-1 is a potential marker for CD disease activity.